Proposed Raised Cosine FMF for Dispersion Management in Next-Generation Optical Networks - Saleh Chebaane; Habib Fathallah; Hussein Seleem; Mohsen Machhout (IEEE Photonics Journal, 2016)
Spatial mode-division multiplexing (MDM) that exploits the emerging few-mode fiber (FMF) technology is one potential candidate for next-generation petabyte optical communication links. In this paper, we focus on the design issues and specifications of the next-generation FMF that will better enable future MDM networks. These systems suffer from two main optical fiber impairments: intermodal coupling and dispersion. In this paper, we focus on the dispersion management issues through an FMF optical link. We first define two potential differential mode group delay (DMD) management strategies, namely, sawtooth and triangular. Moreover, we propose and investigate a novel parametric refractive index profile few-mode fiber, referred to as raised cosine (RC) function, which has been extensively used in digital communication pulse shaping. We investigate the achievable DMD for a wide range of the RC shape parameter and identify the design values of a two-mode FMF fiber. We then improve the RC profile by including additional shaping parameters. This enabled us to develop one four-mode fiber (4-FMF) and one six-mode fiber (6-FMF) having particularly attractive dispersion characteristics for three kinds of FMF applications: nz-, p-, and n-DMD.